2021
DOI: 10.26650/ibr.2021.50.961237
|View full text |Cite
|
Sign up to set email alerts
|

Linking Dynamic Capabilities and Market Performance of SMEs: The Moderating Role of Organizational Agility

Abstract: The purpose of this study is to highlight the moderating role of organizational agility (OA) between dynamic capabilities (DC) and market performance (MP) in SMEs in Turkey and Malaysia. The data was collected from 198 managers in both countries. The data was analyzed by Partial Least Squares Structural Equation Modelling (PLS-SEM). The research has found that there is a significant relationship between organizational agility and market performance, dynamic capabilities and market performance. The finding also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…It also motivates employees to generate innovative ideas about products and services that drive the FP (Škare and Soriano, 2021). Although (Akkaya and Qaisar, 2021; Çallı and Çallı, 2021) found a positive moderation effect on the variables understudy, this study results in contrast with the above study, which found a significant relationship with those variables. Due to factors including capital expenditures, supply chain concerns, and timetables for product development, manufacturing companies often have lengthier planning and execution cycles.…”
Section: Discussioncontrasting
confidence: 99%
“…It also motivates employees to generate innovative ideas about products and services that drive the FP (Škare and Soriano, 2021). Although (Akkaya and Qaisar, 2021; Çallı and Çallı, 2021) found a positive moderation effect on the variables understudy, this study results in contrast with the above study, which found a significant relationship with those variables. Due to factors including capital expenditures, supply chain concerns, and timetables for product development, manufacturing companies often have lengthier planning and execution cycles.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the study will determine how SSCM relates to SM. There is research on information sharing as a moderating variable of SCAG, even though many have advocated for and acknowledged that agility has a favorable influence (Nagel and Dove, 1991;Akkaya and Qaisar, 2021). This research, therefore, addresses the knowledge gaps in these areas.…”
Section: Introduction 1backgroundmentioning
confidence: 94%
“…If businesses want to improve their operational performance in a way that is both sustainable and long-term, they will need to make significant investments in the training and development of their workforce. Akkaya and Qaisar (2021) found that agility serves as a moderating factor. It is generally accepted that SCAG exerts a substantial amount of pressure on the strategic competitiveness of a business.…”
Section: The Moderating Role Of Supply Chain Agilitymentioning
confidence: 99%
“…Economic sustainability for many firms has depended upon their ability to leverage their intellectual capital [2], both formal such as patents and copyrighted materials, and informal such as the knowledge and expertise accumulated by members of the organizations [38]. Likewise, sustainable operations for many firms has depended on their ability to adapt to changes in circumstances both internal and external to their organizations [21,67].…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…Recent studies have paid increasing attention to mechanisms to help managers evaluate needed levels of OA [18], practical methodologies to implement OA [20], the role of OA as a moderator impacting market performance [21], the influence of talent management on OA [22], the relationship between IT capability and OA [23], and factors that either enable or hinder agility [16,24]. Moreover, there is a significant amount of research on agile manufacturing [25][26][27][28][29][30][31][32] and enterprise agility [33].…”
Section: Introductionmentioning
confidence: 99%